Analysis of the employee education system - Pospíšilová, Lucie (2013)
The aim of this bachelor thesis is to analyze the employee education system at the department of management of the European Social Fund at the Ministry of labour and social affairs, to compare the applied education system with the theoretical approaches of the systematic employee education and to propose measures to improve this system in the department. The work is divided into theoretical and practical part. The theoretical part defines the concept and the area of the employee education, includes the description of the process of the systematic employee education and characterizes methods of the employee education. The practical part introduces the Ministry of labour and social affairs as a central body of state administration and analyzes the employee education system at the department of management of the European Social Fund in order to compare this system with the concept of the systematic employee education and to suggest improvement of the existing system.